Measures of health, fitness, and functional movement among firefighter recruits. Issue 2 (3rd April 2017) - Cornell, David J.; Gnacinski, Stacy L.; Zamzow, Aaron; Mims, Jason; Ebersole, Kyle T.
Abstract : Aim . The purpose of this study was to examine the associations between various health and fitness measures and Functional Movement Screen™ (FMS™) scores among 78 firefighter recruits. Methods . Relationships between FMS™ scores and age, body mass index (BMI), sit and reach (S&R) distance, estimated maximal aerobic capacity ( V˙ O2max ), estimated one-repetition maximum squat (1RM-Squatmax ), and plank endurance (%Plankmax ) were examined. Results . Total FMS™ scores were significantly correlated with BMI ( r = −0.231, p = 0.042), estimated 1RM-Squatmax ( r = 0.302, p = 0.007), and %Plankmax ( r = 0.320, p = 0.004). Multiple regression analyses indicated that this combination of predictors significantly predicted ( F (3, 74) = 5.043, p = 0.003) Total FMS™ score outcomes and accounted for 17% of the total variance ( R 2 = 0.170). In addition, logistic regression analyses indicated that estimated 1RM-Squatmax also significantly predicted ( χ 2 = 6.662, df = 1, p = 0.010) FMS™ group membership (≤14 or ≥15). Conclusion . These results suggest that the health and fitness measures of obesity (BMI), bilateral lower extremity strength (estimated 1RM-Squatmax ), and core muscular endurance (%Plankmax ) are significantly associated with functional movement patterns among firefighter recruits. Consequently, injury prevention programs implemented among firefighter recruits should target these aspects of health and fitness.